2017
DOI: 10.7861/clinmedicine.17-6-508
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to HIV testing in people age 50 and above: a systematic review

Abstract: Approximately 13% of people living with HIV in the UK are unaware of their infection. New diagnoses among people ≥50 years is increasing. Unique factors may be associated with testing in this group. This systematic review aims to identify patient and clinician-related barriers/facilitators to HIV testing in people aged ≥50 years. A systematic electronic search was conducted. Papers were assessed for eligibility and data from eligible studies were extracted. Barriers/facilitators were grouped, and the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
3
28
0
2
Order By: Relevance
“…[23][24][25][26] Low perception of HIV risk as well as preconceived ideas about older people by clinicians contribute to lower testing rates as does clinician discomfort exploring HIV risk factors with older patients. 27 However, HIV testing has consistently been found to be acceptable to older people and this study supports the need to increase awareness and improve testing rates for older people and therefore improve outcomes. 28 The lack of a clinically significant increase in testing following our intervention indicates the inadequacy of a single educational intervention in improving testing rates for IC.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…[23][24][25][26] Low perception of HIV risk as well as preconceived ideas about older people by clinicians contribute to lower testing rates as does clinician discomfort exploring HIV risk factors with older patients. 27 However, HIV testing has consistently been found to be acceptable to older people and this study supports the need to increase awareness and improve testing rates for older people and therefore improve outcomes. 28 The lack of a clinically significant increase in testing following our intervention indicates the inadequacy of a single educational intervention in improving testing rates for IC.…”
Section: Discussionsupporting
confidence: 66%
“…However, HIV is a readily treatable condition with an increasing prevalence in older patients and earlier diagnosis in older patients is associated with lower mortality . Low perception of HIV risk as well as preconceived ideas about older people by clinicians contribute to lower testing rates as does clinician discomfort exploring HIV risk factors with older patients . However, HIV testing has consistently been found to be acceptable to older people and this study supports the need to increase awareness and improve testing rates for older people and therefore improve outcomes…”
Section: Discussionsupporting
confidence: 56%
“…In addition to these testing initiatives, there are several other possible reasons for the increasing proportions and rates in those ≥50 years of age, including low rates of condom use among older individuals (21)(22)(23), a lack of prioritization of HIV prevention efforts in older adults (24) and a tendency to a relatively late diagnosis in this population (23), enabling forward transmission. In the United States, older people (≥50 years) are more likely to have late-stage HIV infection at the time of diagnosis, and therefore start treatment later (16).…”
Section: Discussionmentioning
confidence: 99%
“…During the study visit a semi-structured interview was also conducted by EY, lasting approximately 45 min. The initial interview topic guide was based on results of a systematic review which identified patient and clinician-related barriers and facilitators to HIV testing in people aged ≥50 years [ 27 ]. However, novel factors associated with HIV testing were explored within the semi-structured approach, and incorporated into subsequent versions of the topic guide.…”
Section: Methodsmentioning
confidence: 99%